Les réserves de l’internement des adultes dans le droit pénal suisse des mineurs: Une attaque supplémentaire contre les principes de la justice des mineurs - Queloz, Nicolas (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
Contrary to the fundamental principles of Swiss juvenile criminal justice (enshrined in the CRC, the Constitution, the Juvenile Justice Act, and the Juvenile Justice Procedure Act), a “catastrophic” revision of the Juvenile Justice Act will come into force on July 1, 2025. Driven by the ill-advised desire for security at any cost, the federal parliament has continued to undermine the juvenile justice system for more than a decade. These attacks are analyzed below. But the one it adopted on June 13, 2024, is even more severe. It grants jurisdiction, first to the juvenile justice system and then to the adult justice system, to reserve and impose, respectively, upon reaching the age of majority, the serious measure of internment under Art. 64 of the Swiss Criminal Code against a teenager who, while aged 16 or over, committed murder and was sentenced either to placement in a secure institution or to a custodial sentence of three years or more. This intertwining of juvenile and adult criminal law is a sign of an ultra-security strategy. Unfortunately, motions already tabled in the Federal Parliament in Bern show that this strategy will continue, leading to the dismantling of the Swiss juvenile criminal justice system. Without vigorous mobilization by supporters of the educational and emancipatory spirit of juvenile justice, Switzerland will increasingly flout the commitments it made when it ratified the CRC in 1997. (machine translation)